Empowering the Elderly Community through Acupuncture - Suwaji Handaru Wardoyo; Solichan Badri (Universitas Veteran Bangun Nusantara, 2024)
The growth of the elderly population continues to increase every year in line with progress in development and health improvements. The elderly group tends to experience declining health and is likely to have disabilities. Musculoskeletal pain is one of the most common complaints from the elderly population. This service activity aims to provide education regarding pain to the elderly through acupuncture. The acupuncture points used are PC6 Neiguan, SP6 Sanyinjiao, ST36 Zusanli, and LI4 Hequ. This service activity can be said to be successful based on the evaluation carried out. Partners of this service activity said that this activity was very useful and hoped that it would be continued and carried out again. Several community members immediately reported changes in joint pain. Evaluation of simple laboratory examination activities showed that his cholesterol and uric acid levels had improved. Evaluation of the level of understanding of acupuncture for musculoskeletal pain, with repeated implementation, shows that partners can demonstrate acupuncture.